Machining meat deformation - Guts, Viktor; Koval, Olha (My University, 2016)
The mathematical models to optimize the process of salting meat have been determined, the massaging mode method which is based on the energy characteristics in the deformation process has been proposed.
Keywords: кафедра технології ресторанної і аюрведичної продукції; punch pickles; meat massager; deformation; посол; деформація; м'ясний масажер; удар; деформация; мясной массажер